Effectiveness of Dictation Method in Developing English Vocabulary Size: A Study of the 1st Year Business Administration Students, Diploma Program, Rattaphum College, RMUTSV - Aree Tehlah (Journal of Human Development and Communication (JoHDeC), 2025)
The purposes of this study were 1) to investigate the English vocabulary background knowledge of the Business Administration students and 2) to investigate the effectiveness of dictation method in developing English vocabulary size. The subjects in this study were 35 students who studied in Diploma Program of Business Computer, Marketing and Accounting. They enrolled in the English 1 course in the first semester of the academic year 2016. The instrument used was the English vocabulary knowledge pre-test and post-test. Statistical tools used to analyse the data were percentage, mean, standard deviation and independent sample t-test. Results showed that 1) the vocabulary knowledge of students in each major was at a low level, and 2) the dictation method could enhance the students’ English vocabulary size which showed a significant difference at 0.01 levels. This further indicated that the dictation method can help students improve English vocabulary knowledge that encouraged them to learn English in the classroom.